Loop based scheduling for high level synthesis - Al-Sukhni, H.F. (1995)
This paper describes a new loop based scheduling algorithm. The algorithm aims at reducing the runtime processing complexity of path based scheduling techniques. It partitions the control flow graph of the input specification into subgraphs before scheduling the different paths of each subgraph. Benchmark tests as well as simulation results on the scheduling algorithm indicate that the proposed algorithm results in sizeable reduction in runtime